Evaluation of Traumatic Tympan Membrane Perforations - Yamur, Ali Rıza; Özcan, Kürşat Murat (ENT Updates, 2025)
Background: Traumatic tympanic membrane (TM) perforations, although not life-threatening, can significantly impair quality of life by causing hearing loss, tinnitus, and discomfort. These perforations often result from blunt trauma, penetrating trauma, barotrauma, or blast trauma and may be managed either conservatively or surgically, depending on clinical characteristics. Methods: Patients with post-traumatic tympanic membrane perforations were retrospectively evaluated. Trauma type, time of hospital presentation post-trauma, otological complaints at presentation, perforation localization on the membrane, shape, size, and audiometric results were assessed. Results: A total of 48 ears from 47 patients with perforations were evaluated. Most patients (58.3%) presented to the hospital on the first day post-trauma, with initial audiometric evaluation conducted on the same day. Perforations were predominantly in the left ear (58%), anteroinferior quadrant (43.8%), medium-sized (72.9%), and oval/round-shaped (70.8%). Forty-two tympanic membranes underwent repair, while six perforations were managed conservatively. There was no significant difference in perforation healing between the repaired and non-repaired groups at one month post-assessment (p = 1); however, early repair showed statistically superior outcomes compared to late repair (p = 0.01). Conclusion: This study contributes to the literature by comprehensively evaluating clinical characteristics and treatment outcomes of patients with traumatic tympanic membrane perforations, based on single-center, single-surgeon experience. These findings may assist in determining treatment strategies for managing traumatic tympanic membrane perforations.